EFEKTIFITAS PENURUNAN TEMPERATUR DAN INTENSITAS CAHAYA MATERIAL BOTOL KACA BEKAS SEBAGAI DINDING BANGUNAN - Erlangga Putra Dyarie; Intan Findanavy Ridzqo (ITB Ahmad Dahlan Jakarta, 2022)
The deteriorating condition of the earth certainly cannot be separated from garbage and used goods. In this independent research, the focus is on the reuse of used glass bottle materials. This aims to avoid the use of new materials or goods and at the same time become an option to reduce the excessive use of natural resources. The aim of this research is to analyze the effectiveness of reducing temperature and lighting intensity by using used glass bottles as building wall material. The results of this study indicate that the highest thermal decrease is 33% and the highest light intensity decrease is 69%. Not all used glass bottle formations on building wall enclosures are able to reduce temperature and light intensity effectively.